Mothers' perceptions about pediatric dental sedation as an alternative to dental general anesthesia - LIMA,Alessandra Rodrigues de Almeida (2015)
OBJECTIVE: Moderate sedation has limits in managing children's behavior. Existing literature lacks insight into parental perceptions about the topic. This study aimed to understand mothers' perceptions concerning sedation after their children undergone dental treatment under sedation. METHODS: Twelve mothers and one godmother of 1.3-8.4 year-old children with definitely negative behavior in the dental chair, who had dental treatment under oral sedation, were in depth interviewed according to a semi-structured guide. Responses were analysed using a thematic content method and deductive approach. Two general themes were addressed: "good facet" and "poor facet" of pediatric dental sedation. RESULTS: Analysis of interview transcripts indicated that participants perceived pediatric dental sedation according to two main analytical categories: the "good facet" and the "poor facet". The good facet included advantages of the procedure (e.g. safety, effective behavior management), rapport and completion of the treatment that was initially planned. The poor facet related to limitations of moderate sedation (when child kept struggling) and their own anxiety during the procedure. CONCLUSION: Despite their own stress, mothers were satisfied with this pharmacological method of behavior management.